Pengaruh Head Terhadap Kecepatan Dan Debit Aliran Irigasi Tetes Bertingkat Berdasarkan Volume Aliran Tertampung - Negara, I Dewa Gede Jaya; Supriyadi, Anid; Yasa, I Wayan; Suroso, Agus; Akbar, Tabrani (LPPM Universitas Mataram, 2025)
The secondary pipe network in a multi-level drip irrigation network is a water source that will serve the drip irrigation network at each level. The amount of flow obtained by the drip irrigation network is highly dependent on the available head height from the water source. This study aims to determine the amount of flow discharge produced by the height of the water source head in a four-level drip irrigation pipe network, so that it can be used for optimal design of a multi-level drip irrigation network. Optimization of the irrigation network is reviewed against the amount of deviation of discharge from the primary network to the drip discharge, as the final result of irrigation to the plants.Â The test was carried out on a 4-level drip irrigation network with a water source height from the reservoir of 3.21m with a capacity of 200 liters. The head variation consists of four types according to the amount of height of the drip irrigation network to the surface of the reservoir water. The main data analyzed are the volume of flow collected, discharge, speed and deviation of discharge or speed. While the presentation of the results is displayed in the form of regression graphs between the two test parameters, so that they can be applied generally. In the secondary pipe, there is an average difference in flow velocity of around 0.05 m/s in each network, with the lowest secondary flow rate deviation obtained at a small head of 0.2 cm3/s between the fourth and third floors, while the highest discharge deviation is obtained on the first and second floor networks, which is around 1.6 cm3/s. Low vt deviation is obtained at a head below 2.3m and the highest occurs at a head above 2.3m. The difference in head in the primary and secondary distribution networks does not have a significant effect on the distribution of drip irrigation flow, if the drip points are more numerous, the deviation is still within reasonable limits.